Effect of feeding linseed on the fatty acid composition of milk - Süli, Ágnes; Béri, Béla; Csapó, János; Vargáné Visi, Éva (Acta Agraria Debreceniensis, 2013)
In the last decades many researches were made to change the animal product food’s composition. The production of better fat-compound milk and dairy products became a goal in the name of health conscious nutrition. These researches were motivated by the non adequate milk fat’s fatty acid composition. There have been made researches in order to modify the milk’s fatty acids’ composition to reach the expectations of functional foods. With the optimal supplement of the feed can be increased the proportion of the polyunsaturated fatty acids and can decreased the saturated fatty acids. Row fat content of milk was not decreasing in the course of examination neither of the cold extruded linseed nor the whole linseed supplement as opposed to observations experienced by other authors. In case of monounsaturated and polyunsaturated fatty acids when supplementing with cold extruded linseed the most significant change was observable in the concentration of the elaidic acid, oleic acid, linoleic acid, alfa-linolenic acid, conjugated linoleic acid. In case of saturated fatty acids the quantity of palmitic acid and myristic acid lowered considerably. When observating the feeding with whole linseed the concentration of many fatty acids from the milkfat of saturated fatty acids lowered (caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid). The quantity of some unsaturated fatty acids was showing a distinct rise after feeding with linseed, this way the oleic acid, alfa-linolenic acid, conjugated linoleic acid, eicosadienoic acid. The aim of the study was to produce food which meets the changed demands of customers as well. The producing of milk with favourable fatty acid content from human health point of view can give scope propagate the products of animal origin.